Increasing learning interest through android-based word square learning media - Eka Sari Devi; Eka Damayanti; Hamansah Hamansah; Salahuddin Salahuddin; Jamilah Jamilah (Universitas PGRI Semarang, 2022)
The use of media through the Android application is still limited, even though it is needed to foster interest in learning after the COVID-19 pandemic. The research focused on increasing learning interest through the application of the Android-based Word Square learning media. This experimental research used a pretest-posttest control group design. The population in this study were all students of class IX MTs Guppi Samata, which consisted of 2 classes. The saturated sampling method was used in the sampling procedure with six samples taken from the experimental class IX-A and six samples taken from the control class IX-B. The research instrument was a questionnaire consisting of 30 items. The data analysis technique used the Wilcoxon signed ranks test. Students' learning interests differed depending on whether or not they used the Android-based Word Square learning media (p = 0.046, p 0.05). The results showed the differences in students' interest in learning with and without using the media of Word Square learning media based on android human reproductive system material for class IX MTs Guppi Samata (p = 0.046, p < 0.05). The average interest in learning among students through the media was 114.83. The value was higher than those without using the media (106.50). This proves that Word Square learning resources based on Android can increase students' learning interests. The findings of this study can be used to inform teachers' decisions about how to use engaging learning technologies and a variety of media to enhance the quality of their instruction.